1957
DOI: 10.1063/1.1743359
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Spectrum, Structure, and Dipole Moment of s-trans Acrolein

Abstract: The microwave spectrum of acrolein has been studied in the 19–37 kmc region. A series of R-type transitions was identified for the ground and three excited torsional states of the s-trans isomer and these spectra were successfully fitted in the rigid rotor approximation. Using the ground state moments and additional electron diffraction data a reasonable though not unique structure has been obtained. The torsional frequency was found to be 200±50 cm—1 from relative intensity measurements, and a lower limit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

1960
1960
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 6 publications
4
37
0
Order By: Relevance
“…Table 13 shows the comparison of the dipole moments of syn-CH 2 ACHOY and syn-CH 2 AC(CH 3 )OY (Y ϭ NO and CHO). The total observed for syn-2-nitrosopropene was almost the same as that of syn-nitrosoethene (2), within the limits of error, while the total of syn-methacrolein (13) was smaller than that of syn-acrolein (10). It was found that the trend of the total dipole moment of syn-nitrosoethene and syn-acrolein decreases with the methyl effect.…”
Section: Dipole Momentmentioning
confidence: 56%
See 2 more Smart Citations
“…Table 13 shows the comparison of the dipole moments of syn-CH 2 ACHOY and syn-CH 2 AC(CH 3 )OY (Y ϭ NO and CHO). The total observed for syn-2-nitrosopropene was almost the same as that of syn-nitrosoethene (2), within the limits of error, while the total of syn-methacrolein (13) was smaller than that of syn-acrolein (10). It was found that the trend of the total dipole moment of syn-nitrosoethene and syn-acrolein decreases with the methyl effect.…”
Section: Dipole Momentmentioning
confidence: 56%
“…The two rotational isomers of CH 3 CH 2 -Y (Y ϭ NO (8) and CHO (9)) were determined by microwave spectroscopy to be cis ( ϭ 0°) and skew ( ϭ 120°, : dihedral angle of C-C-N-O in CH 3 CH 2 -NO and C-C-C-O in CH 3 CH 2 -CHO) forms. The values of V 3 in cis and skew forms of CH 3 CH 2 -NO (8) were found to be 2578(40) and 2586 (10) cal/mol, while those in cis and skew forms of CH 3 CH 2 -CHO (9) were found to be 2195 (23) and 2532 (29) cal/mol, respectively. The value of V 3 of cis-CH 3 CH 2 -NO was higher than that of cis-CH 3 CH 2 -CHO by ca.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The ENDOR determined structure of Iis identical to the corresponding structure defived ffom X-ray diffraction studies [17]. Wagner and coworkers have estimated that the potential energy of s-trans acrolein is about 2.5 kcal/mol lower than the s-cis conformer, and only about 2 % of the molecules in solution at room temperature are in the s-cis conformation [29]. On this basis we anticipate that the s-trans conformation of II found in this study is similarly energetically favored over the s-cis conformation.…”
Section: Comparison Of Endor Determined Stmctures Of Spin-labeled Dermentioning
confidence: 75%
“…§ Peak-to-peak, channel-to-channel. II References to transition frequencies: 1, Bowater et al (1971); 2, Sorensen (1967); 3, Kirchhoff et al (1971); 4, Wagner et al (1957); 5, Johnson et al (1971).…”
mentioning
confidence: 99%